Effectiveness Of Inspiratory Muscle Training On Vo₂Max: Literature Review - Ni Putu Ayu Dika Utami (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Maximal oxygen uptake (VO₂max) serves as primary indicator of cardiorespiratory capacity among active individuals and athletes. This literature review evaluates effectiveness of inspiratory muscle training (IMT) for enhancing VO₂max and aerobic capacity in healthy/active populations including active children, pre-hypertensive young adults, amateur runners, and artistic athletes. Literature searches conducted across Google Scholar, PEDro, PubMed (2020-2025) using keywords "inspiratory muscle training," "VO2max," "aerobic capacity." Five RCTs with IMT interventions (≥40% maximal inspiratory pressure) reporting VO₂max outcomes included. Five RCTs demonstrate IMT at 50-80% MIP over 4-8 weeks enhances inspiratory strength and aerobic capacity across populations. Active children showed clearest VO₂max gain (+12%); amateur runners exhibited dose-response lactate reduction; artistic athletes gained ventilatory efficiency and performance, pre-hypertensive young adults achieved largest gains (+15%). IMT recommended as complementary modality within cardiorespiratory programs using 50-80% MIP intensity, multiple weekly sessions, minimum 4-week duration. Further research with standardized protocols needed.